Pre-pubertal smoke exposure of fathers and increased risk of offspring asthma: a possible transgenerational effect. Issue 4 (6th October 2022) - Liu, Jiacheng; Bowatte, Gayan; Pham, Jonathan; Perret, Jennifer L.; Holloway, John W.; Lowe, Adrian J.; Burgess, John A.; Svanes, Cecilie; Thomas, Paul; Russell, Melissa A.; Erbas, Bircan; Lodge, Caroline J.; et al.
Asthma is a major non-communicable disease in children [1]. Pre- and post-natal exposure to tobacco smoke are major risk factors for childhood asthma [1, 2]. While there is evidence that mothers' intrauterine exposure to second-hand smoke is associated with asthma in the offspring [3, 4], there is also increasing concern that fathers who start smoking before completing puberty may elevate the risk of asthma in their offspring [4, 5]. The suggestion is that this may be as a result of epigenetic changes to sperm precursor (stem) cells during gonadal maturation [4, 5]. However, this is rather speculative, and as yet little is actually known about whether fathers' passive smoke exposure throughout childhood to puberty is indeed associated with increased asthma risk in their offspring. The risk of non-allergic childhood asthma in offspring may increase if their fathers were exposed to pre-pubertal passive smoke https://bit.ly/3bMHZnP